A Comparison of Medial-congruent, Ultracongruent, and Cruciate-retaining Bearings Using a Single Cruciate-retaining Total Knee Design - Alexander V. Strait, MS; Eric J. Wilson, MD; Henry Ho, MS; Kevin B. Fricka, MD; Robert A. Sershon, MD (Arthroplasty Today)
Background: Improving outcomes has driven advancements in total knee arthroplasty (TKA) bearing design. The aim of this study was to compare medial-congruent (MC), ultracongruent (UC), and cruciate-retaining (CR) TKA utilizing a single CR total knee system. Methods: Six surgeons performed 2883 primary TKAs from 2012 to 2022 using the same implant design, comprised of 708 MC, 799 UC, and 1376 CR bearings. Prospectively collected data on clinical and patient-reported outcome measures were compared. Data analyses utilized analysis of variance tests for continuous data, chi-square tests for categorical data, and Mantel-Cox tests for survivorship analysis. MC subjects were older (MC = 67.5 vs UC = 65.3 vs CR = 66.7 years; P < .001), had lower body mass index (MC = 32.4 vs UC = 33.1 vs CR = 33.2 kg/m2; P = .04), and had shorter mean follow-up (MC = 1.2 vs UC = 2.4 vs CR = 2.9 years; P < .001). Results: All groups experienced similar rates of 90-day complications (MC = 26/708, 3.7% vs UC = 39/799, 4.9% vs CR = 52/1376, 3.8%; P = .38) and revisions (MC = 1/708, 0.1% vs UC = 4/799, 0.5% vs CR = 5/1376, 0.4%; P = .49). Survivorship was similar at 2 years (P = .41) and above 98% at 5 years for all groups. At the 1-year follow-up, MC bearings had significantly greater Patient-Reported Outcomes Measurement Information System Global Health Physical (MC = 47.1 vs UC = 41.5 vs CR = 42.8; P < .001) and mental scores (MC = 48.9 vs UC = 41.3 vs CR = 43.7; P < .001). Conclusions: No differences in all-cause complications or revisions were observed for MC, UC, and CR bearings using the same total knee system. Clinically important differences favoring MC bearings were found with Patient-Reported Outcomes Measurement Information System Global Health Physical scores at 1 year; however, longer follow-up is necessary to determine if this trend holds.